2018
DOI: 10.1007/s11099-017-0745-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humic acid on photosynthetic efficiency of rapeseed plants growing under different watering conditions

Abstract: Water is a limited resource and is likely to become even more restricted with climate change. The aim of this study was to evaluate the effect of humic acid (HA) applications on photosynthesis efficiency of rapeseed plants under different watering conditions. Water stress strongly increased electron transport flux, probability that trapped excitation can move an electron into the electron transport chain beyond Q A , and quantum yield of reduction of end electron acceptors at the PSI acceptor side. Application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 58 publications
(49 reference statements)
4
38
0
Order By: Relevance
“…Fulvic acid spraying improved the Fv/Fm ratio under both watering regimes (Figure 4). These results are similar to those obtained by Lotfi et al (2018), who also reported that FA spraying improves Fv/Fm and the performance index of rapeseed plants under WD and WW conditions. It also increased photosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Fulvic acid spraying improved the Fv/Fm ratio under both watering regimes (Figure 4). These results are similar to those obtained by Lotfi et al (2018), who also reported that FA spraying improves Fv/Fm and the performance index of rapeseed plants under WD and WW conditions. It also increased photosynthesis.…”
Section: Discussionsupporting
confidence: 91%
“…However, a proportion of this energy is released in the form of heat and fluorescence. When the electron transport in the photosynthetic system is partially or completely blocked due to a stress factor, the emitted fluorescence intensity increases, reflecting less use of photosynthetically active radiation by plants [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the photosynthetic efficiency readings collected in the most mature period (60 days PE) showed that the treatments presenting significant differences between control were much closer to the optimal/non-stress threshold. Lotfi et al (2018) tested the effects of HA on photosynthetic efficiency of rapeseed (Brassica napus subsp. napus) plants in different water regimes and the application of HA resulted in increased maximum quantum yield of PSII photochemistry (F v /F m ), where the highest discrepancy between non-humic acid and HA treatments appeared in response to the most severe water stress.…”
Section: Plant Heightmentioning
confidence: 99%